Infrared Thermography for Early Detection of Pepper yellow leaf curl virus on Chili Plants - Triyani Dumaria; Sri Hendrastuti Hidayat; Purnama Hidayat (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2023)
Infrared Thermography for Early Detection of Pepper yellow leaf curl virus on Chili Plants Observations of plant pests and diseases are generally carried out by looking for visual symptoms for each disease target. Agricultural technology 4.0 began to be used for the development of plant disease detection methods. It was reported that there were differences in color and temperature between diseased and healthy plants which could be recorded by a thermal camera. This study aimed to determine the potential of the FLIR One Pro-IOS thermal camera to record differences in color and temperature between viral-infected and healthy chili plants. Chili plants in the greenhouse that were inoculated with Pepper yellow leaf curl virus (PYLCV) experienced an increase in temperature 3 days after inoculation (28.62 ℃) compared to plants that were not inoculated with PYLCV (27.32 ℃). Digital image recording of chili leaf samples from the field showed that plants infected by multiple viruses (Chilli veinal mottle virus, Pepper mottle virus and PYLCV) has higher temperature than those infected with a single virus. The lowest and highest mean temperatures were recorded in plant samples infected with PepMV (17.74 ℃) and mixed infected by PYLCV and ChiVMV (25.68 ℃). Digital images of virus-infected plants tend to show a predominance of bright yellow, while virus-free plants showed a predominance of dark purple. Further analysis confirmed higher digital numbers for diseased plant images than healthy plants. The thermography method has the potential to be an early detection method because it can detect viral infection before visual symptoms appear.